2004
DOI: 10.1177/0890334403261129
|View full text |Cite
|
Sign up to set email alerts
|

Social Capital, Acculturation, and Breastfeeding Initiation Among Puerto Rican Women in the United States

Abstract: To examine reasons for not breastfeeding, and to identify factors associated with ever breastfeeding among Puerto Rican women, a retrospective study was done using a convenience sample of 161 low-income Latino women with children younger than 6 years. Women were recruited from the Hispanic Health Council (43.5%), the Supplemental Nutrition Program for Women, Infants, and Children (29.8%), and other places (26.7%). Participants were interviewed using a pretested questionnaire specific to the target community. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 19 publications
1
40
1
1
Order By: Relevance
“…[2][3][4][5]21,24 Consistent with our findings, previous studies have observed a higher likelihood of breastfeeding associated with increased levels of social support. 18,19 Lower odds of breastfeeding associated with increased levels of acculturation in the general population and among Hispanic women have been observed previously, another finding consistent with our study. 8,21,[25][26][27] This study has certain limitations.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…[2][3][4][5]21,24 Consistent with our findings, previous studies have observed a higher likelihood of breastfeeding associated with increased levels of social support. 18,19 Lower odds of breastfeeding associated with increased levels of acculturation in the general population and among Hispanic women have been observed previously, another finding consistent with our study. 8,21,[25][26][27] This study has certain limitations.…”
Section: Discussionsupporting
confidence: 82%
“…These included gender, parity, household composition, metropolitan/nonmetropolitan residence, parental education, household income or poverty status, neighborhood safety, familial support, maternal physical and emotional health status, maternal physical activity, and household smoking status. [2][3][4][5]7,8,[16][17][18][19] For each relevant covariate, the missing or unknown responses were used as a separate category in regression models instead of excluding them from the multivariate analyses, which would have resulted in a significant decrease in the effective sample size available for analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Perceived early success or failure latching their newborns influenced women's ongoing belief in their bodies' ability to nourish their infants (O'Campo et al, 1992). Other studies have identified problems latching the baby to the breast as a significant predictor of early discontinuation of breastfeeding (Anderson et al, 2004;Cernandas, Noceda, Barrera, Martinez, & Garsd, 2003;DiGirolamo, Grummer-Strawn, & Fein, 2001). Early appropriate help can make the difference in whether a woman continues to breastfeed (Gill, 2001;Mozingo et al, 2000;Tarrant, Dodgson, & Choi, 2002;Whelan & Lupton, 1997).…”
Section: Discussionmentioning
confidence: 92%
“…Compared to white parents, Latino parents believe their children must be older before they can participate in unsupervised activities (Porter et al, 2007). Closer supervision might also result from the presence of extended families and/or social networks (Anderson et al, 2004). While the number of adults in the home were adjusted for, the extent of social networks using the NHIS could not be fully assessed.…”
Section: Discussionmentioning
confidence: 99%